Relationship Between Lifestyle And Hypertension Incidence - Violeta Aulia Hapsari; Hermiaty Nasruddin; Erni Pancawati (Jurnal EduHealth, 2024)
Hypertension is an increase in systolic blood pressure of more than equal to 140 mmHg and diastolic blood pressure of more than equal to 90 mmHg. Hypertension causes the deaths of around 8 million people every year. In Indonesia, Basic Health Research ( Riskesdas ) in 2018 showed an increase in the prevalence of hypertension of around 260 million, namely 34.1% compared to 25.8% in the 2013 Riskesdas . Lifestyle is an important factor that is closely related to the incidence of hypertension, especially in productive age. Unhealthy lifestyles such as diet (salt consumption), lack of physical activity, and smoking can cause hypertension. The aim of this research is to determine the relationship between lifestyle and the incidence of hypertension. This research uses the Literature Review method with a Narrative Review design. Results: This literature review states that there is an influence of lifestyle on the incidence of hypertension. Conclusion: This literature review states that Unhealthy lifestyles such as diet (salt consumption), alcohol, lack of physical activity, and smoking increase the incidence of hypertension.